2016
DOI: 10.1021/acsami.5b10093
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Organic Hole Transporters for Improved Moisture Resistance in Metal Halide Perovskite Solar Cells

Abstract: Solar cells based on organic-inorganic perovskite semiconductor materials have recently made rapid improvements in performance, with the best cells performing at over 20% efficiency. With such rapid progress, questions such as cost and solar cell stability are becoming increasingly important to address if this new technology is to reach commercial deployment. The moisture sensitivity of commonly used organic-inorganic metal halide perovskites has especially raised concerns. Here, we demonstrate that the hygros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 47 publications
(111 reference statements)
5
155
0
Order By: Relevance
“…[237] As result, several groups have focused on the synthesis of hydrophobic HTMs that form pinhole-free films. [208,238,239] This generally results in a reasonable improvement of the stability of the device, with only minor losses of the performance. A particularly interesting strategy has been developed by Habisreutinger et al who employed highly conductive carbon nanotubes encapsulated in a polymer matrix as the charge extraction layer.…”
Section: Moisturementioning
confidence: 96%
See 1 more Smart Citation
“…[237] As result, several groups have focused on the synthesis of hydrophobic HTMs that form pinhole-free films. [208,238,239] This generally results in a reasonable improvement of the stability of the device, with only minor losses of the performance. A particularly interesting strategy has been developed by Habisreutinger et al who employed highly conductive carbon nanotubes encapsulated in a polymer matrix as the charge extraction layer.…”
Section: Moisturementioning
confidence: 96%
“…Especially, the synthesis of the Spiro core in 2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene (Spiro-OMeTAD) requires several steps with a poor overall yield (15 to 30% depending on the synthesis route) [203] and is therefore often replaced by synthetically more accessible cores. Simple moieties such as phenyl, [206] biphenyl, [207] carbazole, [207,208] triphenylamine, [209] or triptycene [210] can be used to reduce the cost, and spiro-based alternatives such as spiro[fluorene-9,9′-xanthene], [211,212] spiro[cyclopenta [2,1- [213] Li et al introduced heteroatoms in the core by using the simple 3,4-ethylenedioxythiophene (EDOT) moiety. Additionally, they were able to perform their reaction in one pot to further reduce the cost.…”
Section: Long-term Viability: Stability and Sustainabilitymentioning
confidence: 99%
“…[18][19][20] Recently, Yang and co-workers demonstrated that inorganic metal oxides can be employed as interfacial materials to enhance the air stability. [18] Bryant et.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…Our perovskite cells composed of p and n-doped organic charge extraction layers are reasonably stable in air (which includes oxygen and moisture) and full spectrum sun light that includes the UV component, which indicates that the perovskite solar cells (this perovskite in this architecture) are not as sensitive to these environmental stressing components as previously thought. [18][19][20][21]49,54,64,65] 2. The n-doping of the C 60 appears to have a persistent beneficial effect over prolonged operation in air, indicating that the N-DPBI retains its doping function throughout the ageing test.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…[21][22][23][24][25][26][27] This can be achieved by replacing the reactive dopants with inert additives such as carbon nanotubes or graphene, 21,28 or by pre-oxidizing a fraction of the hole-transporter in order to improve the charge transport characteristics of the undoped hole-transporting material. 23,29 Nguyen et al could show that by pre-oxidizing a small fraction of spiro-OMeTAD, the overall conductivity of the hole-transporter is increased significantly, yielding device performances comparable to devices with conventional Li-TFSI doping but more stable performance under illumination. 23 Leijtens et al showed that the same technique of partial pre-oxidation can be used on a range of other small-molecule hole-transporters to improve their charge transport characteristics.…”
mentioning
confidence: 99%